2019
DOI: 10.17921/2447-8938.2019v21n4p404-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Dispositions of Resistance Exercises on Subjective Perception of Effort, Discomfort and Affectivity in Older Women

Abstract: The purpose of the study was to verify the effect of two dispositions of resistance exercises on rate of perceived of effort (RPE), discomfort and affectivity in older women. Twenty older women (68.0±6.6 years, 69.8±12.7 kg, and 155.9±7.0 cm) performed in a balanced and randomized design two experimental conditions, namely: a circuit (CIRC) fashion and another in a traditional (TRAD) fashion. In both conditions, six resistance exercises in the following order were performed: push press with kettlebell, swing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…When we evaluated perceived exertion using the Borg scale, the sample reported mild tiredness. Ribeiro et al 22 and Alves et al 23 evaluated women and they reported the same perceived exertion during a walking circuit-based exercise and resistance exercises, considering them easy.…”
Section: Discussionmentioning
confidence: 99%
“…When we evaluated perceived exertion using the Borg scale, the sample reported mild tiredness. Ribeiro et al 22 and Alves et al 23 evaluated women and they reported the same perceived exertion during a walking circuit-based exercise and resistance exercises, considering them easy.…”
Section: Discussionmentioning
confidence: 99%